Evaluación de dependencia funcional en actividades básicas de la vida diaria en pacientes adultos mayores con enfermedad cerebrovascular en el Hospital Regional de Loreto 2019-2020 - Flores Ramírez, Josue Jhoao (2022)
Cerebrovascular disease is a generator of functional dependency in elderly patients, which brings with it personal, family, social and economic repercussions. The objective of the research was to determine at what level the Stroke affects the basic activities of daily life of older adult patients hospitalized at the Regional Hospital of Loreto 2019-2020. The study design was non-experimental, descriptive, retrospective, and cross-sectional; which consisted of 49 elderly patients hospitalized between June 2019 and February 2020 with a diagnosis of CVD, in whom the Barthel index was evaluated. In the results, it was obtained that 53.1% of the population were male; of them, 18.4% had a total dependency; and 46.9% female; of them, 16.3% had mild dependency; 36.7% were between 71 and 80 years old; of these, 10.2% presented total dependency; 71.5% had a partner; 53.1% married, and 18.4% cohabiting. 67.3% had AHT; 20.4% diabetes; CHF and dyslipidemia 10.2% each. 79.6% had an ischemic-type stroke. 30.6% presented total and mild dependence; 16.3% moderate; 14.3% severe; and 8.2% were independent. The aspects with the highest prevalence in functional loss were walking, moving from a wheelchair or bed, ascending and descending stairs, with 79.6%, 75.5%, and 73.5%, respectively. Concluding that the level of affection by CVD in the basic activities of daily life of elderly patients is high, since 91.8% of the population had some degree of dependency.